Telkom Indonesia's Strategy for Business Expansion in the Global Market in the Digital Era - Ali, Rizki Faisal (Global South Review, 2024)
Telecommunications service provider companies face challenges in expanding their business in the global market due to rapidly changing technology, one of which is experienced by PT. Telekomunikasi Indonesia (Telkom). Telkom is a leading telecommunications company in Indonesia that significantly contributes to Indonesia's digitization and dominates the country's telecommunications market. As Telkom's business grows, the company expands globally, with implications for its operations in Indonesia. Based on the globalization strategy framework, the analysis acknowledges that the interaction between globalization and technology, sustainability, and politics poses challenges and opportunities for Telkom. The influence of massive digital transformation requires Telkom to restructure its strategies for expansion in the global market by strengthening its position in the national market. Telkom must ensure its position in Indonesia as a state-owned enterprise with significant responsibility for the future of digital Indonesia as a sustainable influence. Regulations that Telkom must face come from both national and international levels as a result of politics. Telkom's strategy is analyzed using three strategies within the globalization strategy framework. The author proposes several business expansion strategies in the digital era from this research analysisKeywords: digital era; multinational enterprise; global market; globalization; digital telecommunication industry